2013
DOI: 10.3109/14767058.2013.794210
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of tranexamic acid on blood loss in patients undergoing elective cesarean section: randomized clinical trial

Abstract: Pre-operative use of tranexamic acid is associated with reduced blood loss during and after elective cesarean section. This could be of benefit for anemic women or those who refuse blood transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 8 publications
12
103
0
3
Order By: Relevance
“…15 A reduction in postoperative bleeding of around 17% at 2 hours was found in the intervention group, which was significantly less than the almost 25% in IV group tranexamic acid and 23% reduction topical tranexamic group in postoperative blood loss found in the present study Aleem A et al in double blind case control trial who conduct their work upon 740 patients and concluded that the use of tranexamic acid before elective cesarean section is associated with reduced post-partum hemorrhage during and pot elective cesarean section. 16 Also, present results were in agreement with Ahmed et al, Movafegh et al, Goswam et al and Senturk et al [20][21][22][23] The topical tranexamic group demonstrated that topical administration of 2 gm of tranexamic acid in in 2000 ml normal saline at placental bed and uterine scar at cesarean delivery reduced intra-and postoperative blood loss, as well as the amount of intraoperative oxytocin used. Hemoglobin level showed a non-significant r decrease in the control group There was no study in the literature address the role of topical tranexamic acid during cesarean section although Two case reports on the use of topical tranexamic acid to control postoperative local bleeding in 2 women with clotting disorders who were undergoing gynecologic procedures.…”
Section: Discussionsupporting
confidence: 91%
“…15 A reduction in postoperative bleeding of around 17% at 2 hours was found in the intervention group, which was significantly less than the almost 25% in IV group tranexamic acid and 23% reduction topical tranexamic group in postoperative blood loss found in the present study Aleem A et al in double blind case control trial who conduct their work upon 740 patients and concluded that the use of tranexamic acid before elective cesarean section is associated with reduced post-partum hemorrhage during and pot elective cesarean section. 16 Also, present results were in agreement with Ahmed et al, Movafegh et al, Goswam et al and Senturk et al [20][21][22][23] The topical tranexamic group demonstrated that topical administration of 2 gm of tranexamic acid in in 2000 ml normal saline at placental bed and uterine scar at cesarean delivery reduced intra-and postoperative blood loss, as well as the amount of intraoperative oxytocin used. Hemoglobin level showed a non-significant r decrease in the control group There was no study in the literature address the role of topical tranexamic acid during cesarean section although Two case reports on the use of topical tranexamic acid to control postoperative local bleeding in 2 women with clotting disorders who were undergoing gynecologic procedures.…”
Section: Discussionsupporting
confidence: 91%
“…Abdel-Aleem et al [31] used one gm tranexamic acid slowly intravenously over 10 min before elective CS and found the mean drop in hematocrit and hemoglobin levels were significantly lower in TXA group than in control group and concluded that pre-operative TXA is associated with reduced blood loss during and after elective CS. Sentürk et al [32] used TXA 20 cc injected 10 min before the start of CS and found TXA reduced intraoperative and postoperative blood loss without concomitant complications caused by TA such as venous thromboembolism, gastrointestinal problems…”
Section: Resultsmentioning
confidence: 99%
“…En suivant les é tapes dé crites dans la Fig. 1, onze é tudes ont finalement é té incluses dans notre analyse [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Analyse Globale Des Re´sultatsunclassified
“…Parmi celles-ci, 9 é tudes é valuaient l'efficacité d'une administration prophylactique d'acide tranexamique dans le cadre de cé sariennes programmé es [18,19,[21][22][23][25][26][27][28], une é tude é valuait son efficacité en pré vention de l'hé morragie du post-partum lors d'accouchements par voie basse [24] et une seule é tude é valuait l'utilisation d'acide tranexamique dans le traitement de l'hé morragie du post-partum [20] De maniè re gé né rale, les principales caracté ristiques des é tudes incluses dans notre analyse sont ré sumé es dans le Tableau 1. Nous avons constaté que la qualité globale des é tudes é tait bonne avec un risque de biais qui é tait gé né ralement faible (Tableau 2).…”
Section: Analyse Globale Des Re´sultatsunclassified
See 1 more Smart Citation